Structural Basis of Tau Interaction With BIN1 and Regulation by Tau Phosphorylation - Lasorsa, Alessia; Malki, Idir; Cantrelle, François-Xavier; Merzougui, Hamida; Boll, Emmanuelle; Lambert, Jean-Charles; Landrieu, Isabelle (Frontiers in Molecular Neuroscience, 2018)
Bridging integrator-1 (BIN1) gene is associated with an increased risk to develop Alzheimer’s disease, a tauopathy characterized by intra-neuronal accumulation of phosphorylated Tau protein as paired helical filaments. Direct interaction of BIN1 and Tau proteins was demonstrated to be mediated through BIN1 SH3 C-terminal domain and Tau(210-240) peptide within Tau proline-rich domain. We previously showed that BIN1 SH3 interaction with Tau is decreased by phosphorylation within Tau proline-rich domain, of at least T231. In addition, the BIN1/Tau interaction is characterized by a dynamic equilibrium between a closed and open conformations of BIN1 isoform 1, involving an intramolecular interaction with its C-terminal BIN1 SH3 domain. However, the role of the BIN1/Tau interaction, and its potential dysregulation in Alzheimer’s disease, is not yet fully understood. Here we showed that within Tau(210-240) peptide, among the two proline-rich motifs potentially recognized by SH3 domains, only motif P216TPPTR221 is bound by BIN1 SH3. A structural model of the complex between BIN1 SH3 and Tau peptide(213-229), based on nuclear magnetic resonance spectroscopy data, revealed the molecular detail of the interaction. P216 and P219 within the proline-rich motif were in direct contact with the aromatic F588 and W562 of the BIN1 SH3 domain. The contact surface is extended through electrostatic interactions between the positively charged R221 and K224 residues of Tau peptide and those negatively charged of BIN1 SH3, corresponding to E556 and E557. We next investigated the impact of multiple Tau phosphorylations within Tau(210-240) on its interaction with BIN1 isoform 1. Tau(210-240) phosphorylated at four different sites (T212, T217, T231 and S235), contrary to unphosphorylated Tau, was unable to compete with the intramolecular interaction of BIN1 SH3 domain with its CLAP domain. In accordance, the affinity of BIN1 SH3 for phosphorylated Tau(210-240) peptide was reduced, with a 5-fold increase in the dissociation constant, from a Kd of 44µM to 256µM. This study highlights the complexity of the regulation of BIN1 isoform 1 with Tau. As abnormal phosphorylation of Tau is linked to the pathology development, this regulation by phosphorylation might have important functional consequences.